NMDA receptor subunit expression and PAR2 receptor activation in colospinal afferent neurons (CANs) during inflammation induced visceral hypersensitivity - Caudle Robert M; Suckow Shelby K (SAGE Publishing, 2009)
Abstract Background Visceral hypersensitivity is a clinical observation made when diagnosing patients with functional bowel disorders. The cause of visceral hypersensitivity is unknown but is thought to be attributed to inflammation. Previously we demonstrated that a unique set of enteric neurons, colospinal afferent neurons (CANs), co-localize with the NR1 and NR2D subunits of the NMDA receptor as well as with the PAR2 receptor. The aim of this study was to determine if NMDA and PAR2 receptors expressed on CANs contribute to visceral hypersensitivity following inflammation. Recently, work has suggested that dorsal root ganglion (DRG) neurons expressing the transient receptor potential vanilloid-1 (TRPV1) receptor mediate inflammation induced visceral hypersensitivity. Therefore, in order to study CAN involvement in visceral hypersensitivity, DRG neurons expressing the TRPV1 receptor were lesioned with resiniferatoxin (RTX) prior to inflammation and behavioural testing. Results CANs do not express the TRPV1 receptor; therefore, they survive following RTX injection. RTX treatment resulted in a significant decrease in TRPV1 expressing neurons in the colon and immunohistochemical analysis revealed no change in peptide or receptor expression in CANs following RTX lesioning as compared to control data. Behavioral studies determined that both inflamed non-RTX and RTX animals showed a decrease in balloon pressure threshold as compared to controls. Immunohistochemical analysis demonstrated that the NR1 cassettes, N1 and C1, of the NMDA receptor on CANs were up-regulated following inflammation. Furthermore, inflammation resulted in the activation of the PAR2 receptors expressed on CANs. Conclusion Our data show that inflammation causes an up-regulation of the NMDA receptor and the activation of the PAR2 receptor expressed on CANs. These changes are associated with a decrease in balloon pressure in response to colorectal distension in non-RTX and RTX lesioned animals. Therefore, these data suggest that CANs contribute to visceral hypersensitivity during inflammation.